PROFILE OF PATIENTS’ CAREGIVERS IN THE “MELHOR EM CASA” PROGRAM IN THE TOWN OF CERES (CIPEEX, 2024)
Home care (HC) is a form of health care provided in the patient's home and characterized bya series of health promotion, disease prevention, treatment and rehabilitation actions thatguarantee continuity of care and are integrated into the health care network. The “Melhor emCasa” (Better at Home) program was created to assist patients with health problems who havedifficulty or are physically unable to get to medical centers. Guidance for home care can comefrom different services in the care network. The provision of care is the responsibility of amultidisciplinary home care team (EMAD) and a multidisciplinary support team (EMAP),sharing responsibility with family members and/or designated caregivers. Its main goal is toprovide physical, emotional and social assistance to elderly people who need help carrying outdaily activities and maintaining a proper quality of life. The project was carried out in the formof therapeutic groups, at the Home Care Center (SAD), at Praça Curumim and atUniEVANGÉLICA, in the town of Ceres - GO. The groups were held from April to September2023, covering a different theme each month, led by students from the Multidisciplinary Leagueof Ceres (LAMUC). Thus, the following themes were explored: Emotional Care, First Aid,Decubitus Change and Caring for Caregivers - Induced Relaxation. Therefore, a survey wascarried out with nine objective questions to analyze the profile of the caregivers who take partin this program, a total of 33 patients with different pathologies. However, a sample of n=10participants was collected. The final result was as follows: 30% are hired caregivers, 50%family and 20% both; 100% female; 10% between 26-40 years old, 30% from 42-55 years old,60% over 55 years old; 60% are in a conscious mental state, while 40%, unconscious; 50%make use of a GTT tube, 40% oral feeding (solid and liquid) and 10% only liquids; 20% userespiratory support full time, 20% don't and 10% use it occasionally; 60% can communicateverbally, 20% communicate non-verbally (with gestures and blinks) and 20% don'tcommunicate; 70% said they have difficulty changing their position and 30% don't. 90% haddifficulty dressing and dressing; 90% had difficulty bandaging and 10% did not. Nevertheless,it was possible to notice that female family caregivers, aged over 55, caring for patients in aconscious state of mind, who use a GTT tube, who don't need breathing support, whocommunicate verbally, and those who have difficulty changing their position and bandagingtheir wounds, were the ones who prevailed.